Patterns of changing pregnancy intentions among women living with HIV in Canada - Lashanda Skerritt; Angela Kaida; Nadia O'Brien; Ann N. Burchell; Gillian Bartlett; Édénia Savoie; Isabelle Boucoiran; Rebecca Gormley; Mary Kestler; Deborah Money; Mona Loutfy; Alexandra de Pokomandy (BMC, 2021)
Abstract Background Women with an undetectable viral load can become pregnant and have children with no risk of HIV transmission to their sexual partners and low risk of transmission to their infants. Contemporary pregnancy intentions of women living with HIV in Canada are poorly understood, evidenced by high rates of unintended pregnancy and low uptake of contraceptives. Methods We used longitudinal survey data from the Canadian HIV Women's Sexual and Reproductive Health Cohort Study (CHIWOS) to measure and compare pregnancy intentions (Yes vs No vs Unsure) at baseline, 18-months and 36-months follow-up (from 2013 to 2018) among women living with HIV of reproductive age (16-49 years) and potential. We used Sankey diagrams to depict changes in pregnancy intentions over time and multivariable logistic regression to examine the relationship between pregnancy intention within 2 years and subsequent pregnancy. Results At baseline, 41.9% (119/284) of women intended to become pregnant, 43.3% did not, and 14.8% were unsure. Across 36-months of follow-up, 41.9% (119/284) of women changed their pregnancy intentions, with 25% changing from intending to not intending to become pregnant and 13.1% vice versa. Pregnancy intentions were not strongly associated with subsequent pregnancy between baseline and 18-months (aOR 1.44; 95% CI 0.53, 3.72) or between 18 and 36-months (aOR 2.17; 95% CI 0.92, 5.13). Conclusions Our findings underscore the need for healthcare providers to engage in ongoing discussions with women living with HIV to support their dynamic pregnancy intentions.